2011
DOI: 10.1103/physrevb.84.012406
|View full text |Cite
|
Sign up to set email alerts
|

Continuous spin reorientation transition in epitaxial antiferromagnetic NiO thin films

Abstract: Fe/NiO/MgO/Ag(001) films were grown epitaxially and the Fe and NiO spin orientations were determined using X-ray Magnetic Dichroism. We find that the NiO spins are aligned perpendicularly to the Fe spins. Analyzing both the in-plane and out-of-plane spin components of the NiO layer, we demonstrate unambiguously that the NiO spins undergo a continuous spin reorientation transition from the in-plane to out-of-plane directions when tuning the in plane epitaxial strain from compressive to tensile with increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…In thin NiO films, a spin reorientation transition, in which the orientation of the NiO spin changes from being aligned within the film to being perpendicular to the film, is observed [14,15]. This transition depends not only on the thickness of the NiO film, but also on interaction with the support and on temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In thin NiO films, a spin reorientation transition, in which the orientation of the NiO spin changes from being aligned within the film to being perpendicular to the film, is observed [14,15]. This transition depends not only on the thickness of the NiO film, but also on interaction with the support and on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This transition depends not only on the thickness of the NiO film, but also on interaction with the support and on temperature. The spin orientation in thin NiO films may be influenced by epitaxial strain due to lattice mismatch between the film and its (MgO) support [14]. While there are important differences between NiO nanoparticles and thin NiO films, the two systems share the feature that a large proportion of the atoms reside on the surface and by this analogy it is interesting to investigate whether there is a spin reorientation in very thin platelet-shaped particles of NiO.…”
Section: Introductionmentioning
confidence: 99%
“…At d MgO We would like to discuss other possible mechanisms that could affect the exchange bias. First, it is shown that the exchange bias in CoO/Fe system is not directly proportional to the CoO frozen spins [11,12]. Instead, there is a "thickness delay" between the exchange bias and the CoO frozen spins.…”
Section: Resultsmentioning
confidence: 99%
“…By using x-ray magnetic dichroism, it was shown that both the unidirectional reversal characteristic and higher-order anisotropies can be present without the observation of the loop shift 8,44 .…”
Section: Resultsmentioning
confidence: 99%